2016
DOI: 10.1051/bioconf/20160701011
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine yield components and composition of Isabel grape produced according to the organic and conventional systems

Abstract: Abstract. There is an increasing demand for organic grapes by the juice industry of Serra Gaúcha, Brazil. This region presents a humid and hot summer, ideal climatic conditions for the development of a number of diseases. To control such diseases and problems brought about by other organisms, growers apply pesticides on the grapevines which may leave residues in grapes. However, in general, grapes produced by organic system have lower yield, but there is a lack of research data on this subject. Thus, an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Their results indicated that, in the anthocyanin biosynthesis pathway (ABP), genes may be regulated by ABP-specific regulatory factors, and their expression levels may be strongly associated with anthocyanin pigmentation, or they may be expressed independently of pigmentation. It has been known that ‘Isabella’ grape varieties are resistant to fungal diseases and they can be grown in regions with cool and humid climates [ 28 ]. ‘Isabel’ (or Isabella) grape varieties used for grape cultivation in Black Sea region are not affected by fungal diseases, there is no need for the use of drugs in the grape’s cultivation, but some nematodes can cause serious leaf and fruit losses, especially in black ‘Isabel’ grape (reference: personal communication with authorities in Republic of Turkey of Ministry of Agriculture and Forestry-Trabzon Directorate of Agricultural Organization).…”
Section: Resultsmentioning
confidence: 99%
“…Their results indicated that, in the anthocyanin biosynthesis pathway (ABP), genes may be regulated by ABP-specific regulatory factors, and their expression levels may be strongly associated with anthocyanin pigmentation, or they may be expressed independently of pigmentation. It has been known that ‘Isabella’ grape varieties are resistant to fungal diseases and they can be grown in regions with cool and humid climates [ 28 ]. ‘Isabel’ (or Isabella) grape varieties used for grape cultivation in Black Sea region are not affected by fungal diseases, there is no need for the use of drugs in the grape’s cultivation, but some nematodes can cause serious leaf and fruit losses, especially in black ‘Isabel’ grape (reference: personal communication with authorities in Republic of Turkey of Ministry of Agriculture and Forestry-Trabzon Directorate of Agricultural Organization).…”
Section: Resultsmentioning
confidence: 99%